Geographical indications as a territorial development strategy: a braudelian analysis between Brazil and Europe - Wociechoski, Darlan Pez (FCL-UNESP Laboratório Editorial, 2019)
The present work seeks to analyze Geographical Indications as a territorial development policy in Brazilian and European contexts based on the concept of a capitalist world economy, in order to discuss the emergence of a sophisticated way of maintaining the worldwide hierarchy of racial division of labor. Accordingly, the theoretical foundations of Fernand Braudel, Immanuel Wallerstein and Aníbal Quijano are used. We consider, therefore, that geographical indications represent a new form of capital maintenance, since although they generate dynamization and increased income in some semi-peripheral rural territories that were previously disadvantaged by agricultures’ productivist views, these gains are, a priori, lower than the gains of territories from countries of the central nucleus (Europe) that are due to the cultural domination linked to old-world ethnic-racial identities.